Determination of plasminogen/plasmin system components and indicators of lipoproteins oxidative modification under arterial hypertension - O. I. Yusova (Ukrainian Biochemical Journal, 2018)
The present study was investigated of levels of oxidative modification of lipoproteins and content of plasminogen/plasmin system components – tissue-type plasminogen activator (t-PA) and plasminogen activators inhibitor-1 (PAI-I), in patients with stage II arterial hypertension (AHT) and resistant form. It was established that t-PA level in blood plasma of the patients is 2 times lower under stage II hypertension than normal and 2.5 times lower under resistant AHT. The inhibitor activity is 1.5 and 2 times higher consequently. It is concluded that patients with AHT have a decreased fibrinolytic potential, which can cause thrombotic states. Our evaluation showed a significant accumulation of products of lipid and protein oxidation, decrease of activity of antioxidant enzymes and changes of the activity of high density-lipoproteins-associated enzymes (decrease of paraoxonase-1 activity, increase of myeloperoxidase activity). Oxidized lipoproteins, t-PA and PAI-1 can be used as prognostic markers of development of complications and for evaluating the efficacy of therapy in patients with arterial hypertension.